1986
DOI: 10.1021/jm00160a026
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel angiotensin converting enzyme inhibitor quinapril and related compounds. A divergence of structure-activity relationships for non-sulfhydryl and sulfhydryl types

Abstract: The synthesis and angiotensin converting enzyme (ACE) inhibiting activities of quinapril (CI-906, 22), its active diacid (CI-928, 33), and its dimethoxy analogue (CI-925, 25) are reported. These tetrahydro-3-isoquinolinecarboxylic acid derivatives possess equivalent in vitro potency and in vivo efficacy to enalapril. Sulfhydryl analogues with the same structural variation are also highly potent. In contrast, tetrahydro-1-isoquinolinecarboxylic acid and homologous isoindoline-1-carboxylic acid analogues show a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(31 citation statements)
references
References 5 publications
0
27
0
2
Order By: Relevance
“…L 29) or [3S-[2[R*(R*) ],3R*] 1-2-[2-[ [ l -(ethoxycarbonyl)-3-phenylpropyl]amino]-1 -oxopropyl]-1,2,3,4-tetrahydro-6,7-dimethoxy-3-isoquinolinecarboxylic acid, monohydrochloride was synthesized by Hoefle and Klutchko (15,19). Moexipril hydrochloride is a white powder with a molecular weight of 535.04 and a melting point of 155°C to 160°C.…”
Section: Chemistry and Pharmacologymentioning
confidence: 99%
“…L 29) or [3S-[2[R*(R*) ],3R*] 1-2-[2-[ [ l -(ethoxycarbonyl)-3-phenylpropyl]amino]-1 -oxopropyl]-1,2,3,4-tetrahydro-6,7-dimethoxy-3-isoquinolinecarboxylic acid, monohydrochloride was synthesized by Hoefle and Klutchko (15,19). Moexipril hydrochloride is a white powder with a molecular weight of 535.04 and a melting point of 155°C to 160°C.…”
Section: Chemistry and Pharmacologymentioning
confidence: 99%
“…Enfin, les quatre synthkses d'isoquinoltines acyltes en position 3 reportees dans la litttrature cornportent de nombreuses ttapes et la prtparation prtalable d'isoquinoltines substituCes en position 3 par un reste de type halogkne (22,23), mtthyle (24) ou carboxylate d'tthyle (25). Enfin les multiples possibilitCs synthttiques au depart des cttones rendent notre mtthode particulierement inttressante pour acceder 2 la famille des isoquinoltines substitutes en position 3, composts qui ont Ct C ttudiCs en tant qu'inhibiteurs d'enzymes (26), intermtdiaires de synthbe (27), ou modkles biologiques (25). Ajoutons egalement que certains mttabolites fongiques appartiennent cette classe d'htttrocycles (28).…”
Section: Ar-chunclassified
“…A strategy which has now been applied successfully in several cases is replacing the proline residue with Tic residue [42][43][44][45][46]. In 1983, Hayashi and co-workers reported that the in vitro ACE inhibitory activity of compound 55 was more potent than its precursor captopril, and the in vivo activity and hypotensive effects of compound 55 were also comparable to captopril [42].…”
Section: Utilization In Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 99%
“…The most successful case was the optimization of enalapril, which led to another more potent approved drug quinapril 57, Fig. (11) [46]. Generally, hydrophobic compounds are more potent.…”
Section: Utilization In Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 99%